ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN E-POP UP BOOK BERBASIS KEARIFAN LOKAL KOTA TRENGGALEK MATERI SIKLUS AIR UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Asriningrum, Yuyun Diyah; Aka, Kukuh Andri; Primastya, Nurita (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
Abstract: Needs analysis is the initial activity to achieve learning objectives, including one of them in science learning. Needs analysis conveys in-depth information as a reference for developing learning media. The purpose of this study was to analyze the need for the development of E-pop up book learning media based on Local Wisdom of Trenggalek city for grade V students of SDN 2 Sukokidul. This development research uses descriptive analysis method, questionnaire instrument as data collection. Based on the results of this study, it can be concluded that the results of the needs analysis of the media development of E-pop up Book learning media based on Local Wisdom of Trenggalek City received a positive response. This research can be developed in the development of E-pop up book learning media for water cycle material based on Trenggalek City Local Wisdom for grade V students of SDN 2 Sukokidul. Keywords: Needs analysis, E-pop up book media, Water cycle, Local Wisdom